Building green loyalty through sustainable marketing: Evidence from generation Z consumers in the Bandung-Indonesian cosmetics market - Putri, Melati Wahyudina; Pradana, Mahir; Widodo, Arry (Edelweiss Applied Science and Technology, 2025)
Rising environmental consciousness among consumers, particularly within Generation Z demographics, has catalyzed the cosmetics industry's transition toward sustainable marketing methodologies. The Body Shop, recognized as a pioneering entity in environmental marketing strategies, serves as an exemplary case study for understanding consumer attraction to environmentally responsible brands. This research examines the mechanisms through which green marketing practices influence consumer loyalty, with specific emphasis on the mediating functions of green brand image, green trust, and green satisfaction. The investigation employed a survey methodology encompassing 435 The Body Shop customers in Bandung, utilizing partial least squares structural equation modeling (PLS-SEM) for comprehensive data analysis. Findings demonstrate that green marketing mix strategies exert substantial influence on green brand image (β = 0.638), green trust (β = 0.622), and green satisfaction (β = 0.603), collectively contributing to enhanced green loyalty (R² = 0.676). This study expands theoretical understanding and provides practical insights for cosmetic industry practitioners by examining three mediating variables simultaneously within an integrated green marketing framework. Additionally, this study contributes theoretically to expanding sustainable marketing models and offers practical implications for the cosmetic industry in designing strategies that emphasize enhancing consumer satisfaction, building trust, and improving brand image.